Efektivitas Media Video Pembelajaran Pembuatan Chiffon Cake Terhadap Hasil Belajar Mahasiswa D3 Tata Boga Pada Mata Kuliah Kue Kontinental - Mahdiyah; Guspri Devi Artanti; Rijki Purnama (Jurnal Sains Boga, 2020)
The purpose of this research is to study the effectiveness of video learning media for making chiffon cakes for learning outcomes from D3 Food Catering students in continental pastry class, Universitas Negeri Jakarta. The population in management of continental pastry class is students who are taking continental cake class, and the respondent of this research is 44 student. The method used in the this research is quasi experiment. The results of this reserach are that the experimental class group learning outcomes show an average value of 67.65 for pre-test 80.24 for post-test scores increasing 12.58 or 15.69% and for the control class of 67.82 for pre-test 74.29 for post-test scores increasing 6.46 or 8.71% and for the group skills in experimental class, the average value was 86.13 and for the control group was 79.13. Thus it can be conluded that there is an influence from learning video about chiffon cake making towards the learning outcomes of food and nutrition student in continental pastry class.